Comparison of the Insertion Conditions and Haemodynamic Changes during I-Gel Insertion using Propofol, Ketamine-Propofol (Ketofol) and Thiopentone Intravenous Induction Agents: An Interventional Study - Pooja Arpapan Shah; Aashi Nilesh Surti; Anupapama Kumari; Dinesh K Chauhan; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: The I-gel was designed to mitigate adverse reactions by providing the advantages of a secure airway without the complications associated with visualisation and tracheal intubation, specifically reducing the risk of barotrauma and vocal cord damage. Insertion requires a good induction agent and adequate depth of anaesthesia to achieve proper jaw relaxation and to prevent effects such as coughing, gagging, laryngospasm and any movements. Induction agents like propofol, ketamine and thiopentone have facilitated Laryngeal Mask Airway (LMA) insertion with ease. Aim: To compare insertion conditions and haemodynamic changes during I-gel insertion using propofol, ketamine-propofol (ketofol) and thiopentone as intravenous induction agents. Materials and Methods: An interventional study was conducted at a tertiary care hospital, Anaesthesiology Department of Dhiraj General Hospital in Piparia, Vadodara, Gujarat, India from August 1, 2023, to July 31, 2024. within one year after receiving ethical clearance from the institutional ethical committee. A total of 36 patients with American Society of Anaesthesiologists (ASA) physical status I and II, aged 18-60 years, were randomly divided into three groups. The induction agents administered before I-gel insertion for general anaesthesia in groups 1, 2 and 3 were propofol (2 mg/kg), ketofol (1 mg/kg ketamine and 1 mg/kg propofol) and thiopentone (4 mg/kg), respectively. Intubating conditions such as jaw mobility, number of attempts, ease of insertion, duration of insertion and haemodynamic response during I-gel insertion were recorded. The Kruskal-Wallis test and Chi-square test were used for quantitative and qualitative parameters, respectively. A p-value of ≤0.05 was considered statistically significant. Results: The mean age of Group-1, Group-2 and Group-3 was 34.67±5.97 years, 33.25±8.70 years and 36±8.48 years, respectively. Complete jaw relaxation and mouth opening were better in the ketofol group than in the propofol group (p-value: 0.003) and were significantly lower in the thiopentone group. Induction time was faster in the ketofol group than in the other groups. Patients in the ketofol and propofol groups exhibited better intubating conditions and preserved haemodynamics following I-gel insertion compared to those in the thiopentone group. Conclusion: Compared to propofol and thiopentone, ketofol demonstrated a faster onset of action and ensured better insertion conditions and greater haemodynamic stability, making it a preferred choice for I-gel insertion.